Surgical applications of intracorporal tissue adhesive agents: current evidence and future development. (3rd May 2020) - Gillman, Nicholas; Lloyd, David; Bindra, Randy; Ruan, Rui; Zheng, Minghao
ABSTRACT: Introduction : Traditional mechanical closure techniques pose many challenges including the risk of infection, tissue reaction, and injury to both patients and clinicians. There is an urgent need to develop tissue adhesive agents to reform closure technique. This review examined a variety of tissue adhesive agents available in the market in an attempt to gain a better understanding of intracorporal tissue adhesive agents as medical devices. Areas covered : Fundamental principles and clinical determinants of the tissue adhesives were summarized. The available tissue adhesives for intracorporal use and their relevant clinical evidence were then presented. Lastly, the perspective of future development for intracorporal tissue adhesive were discussed. Clinical evidence shows current agents are efficacious as adjunctive measures to mechanical closure and these agents have been trialed outside of clinical indications with varied results. Expert opinion : Despite some advancements in the development of tissue adhesives, there is still a demand to develop novel technologies in order to address unmet clinical needs, including low tensile strength in wet conditions, non-controllable polimerization and sub-optimal biocompatibility. Research trends focus on producing novel adhesive agents to remit these challenges. Examples include the development of biomimetic adhesives, externally activated adhesives, and multiple crosslinking strategies. Economic feasibility and biosafety are limiting factors for clinical implementation.